Complying with Europe EU harmonisation and soft law in the member states - Falkner, Gerda (Themes in European governance, 2005)
What does EU law truly mean for the member states? Do they abide or don't they? This book presents the first encompassing and in-depth empirical study of the effects of 'voluntaristic' and (partly) 'soft' EU policies in all 15 member states. The authors examine 90 case studies across a range of EU Directives and shed light on burning contemporary issues in political science, integration theory, and social policy. They reveal that there are major implementation failures and that, to date, the European Commission has not been able adequately to perform its control function. While all countries are occasional non-compliers, some quite frequently privilege their domestic political concerns over performance of their EU-related duties. Others neglect these EU obligations as a matter of course. This study answers questions of crucial importance for politics in theory and in practice, and suggests how implementation of EU law can be fostered in the future